Respostas
respondido por:
3
(x-y)² =0,6
x²-2xy+y²=0,6
x²-2.4+y²=0,6
x²+y²=0,6+8
x²+y²=8,6
lembre-se de produtos notáveis
x²-2xy+y²=0,6
x²-2.4+y²=0,6
x²+y²=0,6+8
x²+y²=8,6
lembre-se de produtos notáveis
respondido por:
0
Se: (x – y)^2 = 0,6 e xy = 4, calcular o valor de
x^2 + y^2 = ?
Então: (x – y)^2 = 0,6 => (x – y). (x – y) = 0,6 => x^2 – 2xy + y^2 = 0,6 => x^2 + y^2 – 2.4 = 0,6 => x^2 + y^2 – 8 = 0,6 => x^2 + y^2 = 0,6 + 8 => x^2 + y^2 = 8,6
Espero ter-lhe ajudado
Então: (x – y)^2 = 0,6 => (x – y). (x – y) = 0,6 => x^2 – 2xy + y^2 = 0,6 => x^2 + y^2 – 2.4 = 0,6 => x^2 + y^2 – 8 = 0,6 => x^2 + y^2 = 0,6 + 8 => x^2 + y^2 = 8,6
Espero ter-lhe ajudado
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás